"EFFECT OF CEFTAZIDIME ON HAEMATOLOGICAL AND BIOCHEMICAL PARAMETERS USING ALBINO WISTAR RAT" - ABHISHEK PRATAP SINGH,; SAUMYA DAS, (International Journal of Pharma and Bio Sciences, 2016)
The aim of present study was to determine the changes in biochemical and haematological parameters in healthy Albino Wistar rat after 14-day parenteral treatment with Ceftazidime, a third generation cephalosporin. For the hematological and biochemical studies of Ceftazidime, two groups of animals containing five in each group were taken. One group was control (Group I) while other group was treated (Group II). The animals were treated at intervals of 24h for 14 consecutive days. All doses were injected subcutaneously. Blood samples for evaluation of biochemical and haematological parameters were collected on 1st, 7th and 14th day after treatment. Blood collection was done through retro-orbital site. All the blood samples were collected in EDTA coated vacutainer for RBC counts, total WBC counts, and haemoglobin along with Eosinophiles, Lymphocytes, Monocytes, Basophiles and blood glucose level. For biochemical parameters i.e. Serum Glutamic Oxaloacetic Transaminase (SGOT) and Serum Glutamic Pyruvic Transaminase (SGPT) blood sample was send to commercial laboratory. The drug didn’t affect the blood glucose level of the treated rats. The value of SGOT and SGPT was continuously increasing, it means the drug effect the liver enzymes of treated rats. From this study it was concluded that Ceftazidime cause thromocytopenia, neutropenia, lymphocytosis, leukocytosis, eosinophila.